Mary Colter au Grand Canyon ou l’invention d’un paysage - Patrick Pérez (Projets de Paysage)
The Arizona Grand Canyon is one of the most spectacular sites on the planet. Yet it took four centuries to form the vision of this landscape as we know and share it today. Discovered in 1540, the Canyon was immediately forgotten before becoming in the middle of the 19th century the focus of minutely detailed scientific exploration and in the beginning of the 20th century an American monument. For it to become an admired landscape embedded in the practise of tourism, a shared aesthetic perception needed to be built. Scientists, painters, and photographers were the artisans of the first taming of this landscape. But it is undoubtedly the architect Mary Colter who, in the space of thirty years (1905-1935), built the exceptional visual system which enables us to see the Grand Canyon as we perceive it today. This article conducts a detailed analysis of the construction of this visualisation of the landscape.